EKO-EDUKASI GIZI ATLET MUDA: PENDIRIAN KEBUN SEKOLAH BERBASIS TANAMAN LOKAL DAN KEBUN CERDAS BERSENSOR DI SEKOLAH KHUSUS OLAHRAGA PAPUA - Tri Setyo Guntoro; Desy Anita Karolina Sembiring; Agus Zainuri; Renata Anastasya Engelique Ngaderman; Skolastika Jelita; Ansar CS; Ermelinda Yersin Putri Larung; Miftah Fariz Prima Putra; Evi Sinaga (Universitas Mataram, 2026)
Special Sports Schools (SKO) face numerous challenges in achieving human resource development objectives through sports education, particularly regarding infrastructure, nutrition management, and professional workforce availability, with the root of nutritional issues at Papua SKO lying in athlete nutrition management during young athlete development. Conversely, SKO possesses substantial land suitable for conversion into school gardens that can subsequently serve as sustainable nutritional and energy sources for students. This Community Service (PkM) program therefore aimed to: provide education and training on sports nutrition management, deliver school garden establishment training, and conduct athlete nutrition education, implemented through sequential stages of socialization, training, technology application, mentoring and evaluation, and sustainability planning during June-October 2025 with 45 students and 5 teachers/coaches participating. Implementation involved socializing the school garden concept, training on simple irrigation systems and smart gardens utilizing moisture sensors and plant growth monitoring, followed by comprehensive mentoring and evaluation, resulting in 80% of students understanding sports nutrition and school garden concepts while 83% could establish gardens using simple irrigation techniques, with understanding demonstrated through significant knowledge improvement from pre-test scores (49.96±6.55) to post-test (90.14±6.16), a mean difference of 40.18±7.21, and N-Gain of 0.80. The integrative approach successfully addressed fundamental nutritional understanding and availability issues for young athletes, creating a sustainable solution through combined nutrition education and school gardening that concurrently alleviated infrastructure limitations.